Stochastic simulation of physicochemical processes performance over supported metal nanoparticles - Kovalyov, Evgenii V (Journal of computational chemistry, 2008)
The statistical lattice model has been proposed which permits one to take into account the change in the shape and surface morphology of the nanoparticle under the influence of the reaction media. The influence of monomolecular and dissociative adsorption on the particles equilibrium shape and surface morphology has been studied. It has been shown that by taking into account of attraction "adsorbate-metal" the reshaping of the initial hemispheric particle into cone-shaped one occurs induced by adsorption, similar to the experimentally observed reversible reshaping of active nanoparticles. The model reaction A+B(2) has been studied taking into account the roughening of the active particle surface and the spillover phenomena of the adsorbed A(ads) species over the support surface